The study on Chinese MNEs’ internationalization toward OFDI - NI, CHENGYUAN (2014)
Abstract Over the past 20 years, China’s outward foreign direct investment has a substantial growth and more and more Chinese multinational enterprises have conducted internationalization and have created a huge amount of overseas investment. This paper aims to examine the main features of Chinese multinational enterprises’ internationalization toward outward foreign direct investment and to explore the applicability of some mainstream theories on Chinese MNEs’ internationalization. Adopting a case study research method, four cases companies has been chosen they are Lenovo, Galanz, Haier and TCL. This paper had examines several key elements which are highly related to these Chinese firms’ internationalization, they are the internationalization drivers, the overseas expansion process and the firm specific ownership advantages. Moreover, combining the case analysis with the evaluation of five mainstream internationalization theories (the Stage Theory, the Uppsala Model, the Innovation-Related Model, Internalization Theory and Dunning’s Eclectic Paradigm) a lot of research findings have been showed in this paper. One finding from this research indicates that Chinese multinational firms have a common motivation of internationalization, which is to seek strategic assets. This finding is inconsistent with the mainstream theory as in these theories, firm conduct internationalization to exploit their firm-specific ownership advantage, instead to enhance or obtain ownership advantage. Moreover, other finding are also indicated that the conventional internationalization theorise are not fully suitable to explain current firms’ internationalization especially to those from emerging economies such as Chine. Therefore, a special theory is needed to explain the Chinese multinational firms’ internationalization. Moreover, the limitation of this research and future avenues for further studies and researches are also been provided.